Central Sensitization and Pain: Pathophysiologic and Clinical Insights - Curatolo, Michele (Current Neuropharmacology, 2024)
Central sensitization is an increased responsiveness of nociceptive neurons in the central nervous system to their normal or subthreshold afferent input. Aim: To explain how the notion of central sensitization has changed our understanding of pain conditions, discuss how this knowledge can be used to improve the management of pain, and highlight knowledge gaps that future research needs to address. Methods: Overview of definitions, assessment methods, and clinical implications. Results: Human pain models, and functional and molecular imaging have provided converging evidence that central sensitization occurs and is clinically relevant. Measures to assess central sensitization in patients are available; however, their ability to discriminate sensitization of central from peripheral neurons is unclear. Treatments that attenuate central sensitization are available, but the limited understanding of molecular and functional mechanisms hampers the development of target-specific treatments. The origin of central sensitization in human pain conditions that are not associated with tissue damage remains unclear. Conclusion: The knowledge of central sensitization has revolutionized our neurobiological understanding of pain. Despite the limitations of clinical assessment in identifying central sensitization, it is appropriate to use the available tools to guide clinical decisions towards treatments that attenuate central sensitization. Future research that elucidates the causes, molecular and functional mechanisms of central sensitization would provide crucial progress towards the development of treatments that target specific mechanisms of central sensitization.
Keywords: pain therapy